Future Space-Transport-System Components under High Thermal and Mechanical Loads Results from the DFG Collaborative Research Center TRR40 - Adams, Nikolaus A.; Schröder, Wolfgang; Radespiel, Rolf; Haidn, Oskar J.; Sattelmayer, Thomas; Stemmer, Christian; Weigand, Bernhard (Notes on Numerical Fluid Mechanics and Multidisciplinary Design, 2021)
This open access book presents the findings of Collaborative Research Center Transregio 40 (TRR40), initiated in July 2008 and funded by the German Research Foundation (DFG). Gathering innovative design concepts for thrust chambers and nozzles, as well as cutting-edge methods of aft-body flow control and propulsion-component cooling, it brings together fundamental research undertaken at universities, testing carried out at the German Aerospace Center (DLR) and industrial developments from the ArianeGroup. With a particular focus on heat transfer analyses and novel cooling concepts for thermally highly loaded structures, the book highlights the aft-body flow of the space transportation system and its interaction with the nozzle flow, which are especially critical during the early phase of atmospheric ascent. Moreover, it describes virtual demonstrators for combustion chambers and nozzles, and discusses their industrial applicability. As such, it is a timely resource for researchers, graduate students and practitioners. .